The Oriental bamboo-feeding genus Bambusiphaga Huang & Ding, 1979 (Hemiptera: Delphacidae: Tropidocephalini): a checklist, a key to the species and descriptions of two new species - Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2011)
A checklist of the known species of the Oriental bamboo-feeding genus Bambusiphaga Huang & Ding, 1979 (Hemiptera: Fulgoromorpha: Delphacidae: Delphacinae: Tropidocephalini) together with their host plants and geographical distribution and a key to the known species in the genus are provided. Two new species, B. kunmingensis sp. nov. and B. yangi sp. nov., are described and illustrated from Yunnan Province, southwestern China.